Scrub Nurse's Performance Concerning Surgical Aseptic Techniques at the Operating Room of Slemani Teaching Hospitals - Farida AbdulKader Taher; Samir younis Lafi (مجلة الموصل للتمريض, 2015)
Background and aim: the study aims is to assess the level of performance among the scrub nurses concerning the surgical aseptic techniques at the operating room, describe the socio- demographic characteristics of the study sample, and to find out the relationship between the scrub performance and variables of some demographic characteristics such as (age, gender, level of education, marital status, and years of experience in operating room). Materials and method: quantitative design, non - probability (purposive) sample of (70) male and female scrub nurses who worked at three teaching hospitals, which represent vital agencies in Slemani city (Iraqi Kurdistan rejoin), during the period of December 2009 up to the end of September 2010. Data were collected through two types of instruments (questionnaire and observational checklist); the researcher modified the study instrument to investigate the scrub nurses practices in the three teaching hospitals: It was based on extensive review of related literature and studies. The study instruments compressed of seven dimensions which include total of (91) items, the content validity of the instrument was established through penal of (20) experts. Reliability of the instrument was determined through the use of equivalence reliability, Inter- rater (Inter observer) approach, (r=0.91). Data were analyzed through the application of descriptive and inferential statistical analysis. Results: the result of the study revealed that the most of the nurses are middle – aged, married female, with a low level of monthly income. The majority of the study sample is institute graduates and they have no long employment in operating room. Most of the study sample has poor skills in scrubbing practices. Furthermore, the study confirms that there is a significant relationship between the economic status and their practices. Recommendations: based on the results of the study, the study recommended that job description have to be legislated to all nursing categories as one of job for better achievement and a periodic in service, educational program for operating room nurses and certified to identify the qualified ones. Further study should be carried out to be recommended to develop operating room work achievements. Keywords: Scrub, Aseptic techniques.